On educational performance measures - Alastair Muriel; Jeffrey A. Smith (Institute for the Study of Labor (IZA), 2011)
Quantitative school performance measures (QPMs) are playing an ever larger role in education systems on both sides of the Atlantic. In this paper we outline the rationale for the use of such measures in education, review the literature relating to several important problems associated with their use, and argue that they nonetheless have a positive role to play in improving the educational quality. We delineate several institutional reforms which would help schools to respond positively to QPMs, emphasizing the importance of agents' flexibility to change the way they work, and the importance of a sound knowledge base regarding what works in raising attainment. We suggest that the present institutional setups in both England and the US too often hold schools accountable for outcomes over which they have little control - but that such problems are far from insurmountable.
urn:nbn:de:101:1-201108152046
Keywords: H52; I2; I28; 330; school quality; performance measures; education incentives